KELAYAKAN MEDIA E-COMIC PADA SUBMATERI SISTEM ENDOKRIN KELAS XI SMA - Galuh Retno Purnamasari; Ruqiah Ganda Putri P; Eko Sri Wahyuni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis research aims to determine the feasibility of e-comic on the submaterial Endocrine System in XI grade of Senior High School. The methods used in this research was descriptive research survey form. Research instrument used was sheet validation. The eligibility of  e-comic was measured through validity test by 6 validator consists of 3 person material expert validator and 3 media expert validator. The validity test of material expert covering aspects of the format, content, and language with an average of every aspect of 3.66; 3.66; and 4, while testing the validity of media expert covering aspects of simplicity, alignment, balance, form, and color with an average of every aspect of 4; 4; 3.66; 3.66; and 4. The e-comic validation result was obtained an average validation value of material was 3.77 and an average validation value of media was 3,86. It could be concluded  that e-comic was feasibility to be used as learning media on the submaterial Endocrine System in grade XI of Senior High School.Keywords: feasibility, e-comic, submaterial, endocrine system.